Schwann cell-mediated delivery of glial cell line-derived neurotrophic factor restores erectile function after cavernous nerve injury - May, Florian; Buchner, Alexander; Schlenker, Boris; Gratzke, Christian; Arndt, Christian; Stief, Christian; Weidner, Norbert; Matiasek, Kaspar (International journal of urology, 2013)
Objectives To evaluate the time-course of functional recovery after cavernous nerve injury using glial cell line-derived neurotrophic factor-transduced Schwann cell-seeded silicon tubes. Methods Sections of the cavernous nerves were excised bilaterally (5 mm), followed by immediate bilateral surgical repair. A total of 20 study nerves per group were reconstructed by interposition of empty silicon tubes and silicon tubes seeded with either glial cell line-derived neurotrophic factor-overexpressing or green fluorescent protein-expressing Schwann cells. Control groups were either sham-operated or received bilateral nerve transection without nerve reconstruction. Erectile function was evaluated by relaparotomy, electrical nerve stimulation and intracavernous pressure recording after 2, 4, 6, 8 and 10 weeks. The animals underwent re-exploration only once, and were killed afterwards. The nerve grafts were investigated for the maturation state of regenerating nerve fibers and the fascular composition. Results Recovery of erectile function took at least 4 weeks in the current model. Glial cell line-derived neurotrophic factor-transduced Schwann cell grafts restored erectile function better than green fluorescent protein-transduced controls and unseeded conduits. Glial cell line-derived neurotrophic factor-transduced grafts promoted an intact erectile response (4/4) at 4, 6, 8 and 10 weeks that was overall significantly superior to negative controls (P < 0.001). Maximum intracavernous pressure on electrostimulation was significantly elevated using glial cell line-derived neurotrophic factor-transduced grafts compared with negative controls (P = 0.018) and unseeded tubes (P = 0.034). Return of function was associated with the electron microscopic evidence of preganglionic myelinated nerve fibers and postganglionic unmyelinated axons. Conclusions Schwann cell-mediated delivery of glial cell line-derived neurotrophic factor presents a viable approach for the treatment of erectile dysfunction after cavernous nerve injury.